2021
DOI: 10.3390/jdb9040044
|View full text |Cite
|
Sign up to set email alerts
|

MEIS1 in Hematopoiesis and Cancer. How MEIS1-PBX Interaction Can Be Used in Therapy

Abstract: Recently MEIS1 emerged as a major determinant of the MLL-r leukemic phenotype. The latest and most efficient drugs effectively decrease the levels of MEIS1 in cancer cells. Together with an overview of the latest drugs developed to target MEIS1 in MLL-r leukemia, we review, in detail, the role of MEIS1 in embryonic and adult hematopoiesis and suggest how a more profound knowledge of MEIS1 biochemistry can be used to design potent and effective drugs against MLL-r leukemia. In addition, we present data showing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 148 publications
1
3
0
Order By: Relevance
“…Overexpression of MEIS1/PBX3 is sufficient for transformation of mouse hematopoietic stem cells and driving AML in vivo, as previously reported 48 . Moreover, elevated expression of HOXA9 and MEIS1 genes is associated with a number of hematological malignancies, suggesting that these genes are involved in the development of a variety of leukemias 49–51 . Patients with high MEIS1 expression have shorter survival times than those with low MEIS1 , indicating that MEIS1 expression could be a prognostic factor even in AMLs with normal karyotype 50 , 52 .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Overexpression of MEIS1/PBX3 is sufficient for transformation of mouse hematopoietic stem cells and driving AML in vivo, as previously reported 48 . Moreover, elevated expression of HOXA9 and MEIS1 genes is associated with a number of hematological malignancies, suggesting that these genes are involved in the development of a variety of leukemias 49–51 . Patients with high MEIS1 expression have shorter survival times than those with low MEIS1 , indicating that MEIS1 expression could be a prognostic factor even in AMLs with normal karyotype 50 , 52 .…”
Section: Discussionsupporting
confidence: 64%
“…48 Moreover, elevated expression of HOXA9 and MEIS1 genes is associated with a number of hematological malignancies, suggesting that these genes are involved in the development of a variety of leukemias. [49][50][51] Patients with high MEIS1 expression have shorter survival times than those with low MEIS1, indicating that MEIS1 expression could be a prognostic factor even in AMLs with normal karyotype. 50,52 In this context, it is interesting to note that Menin inhibition has profound antileukemic effects in MLL-r, NPM1-mutant, and NUP98-r acute leukemias where MEIS1/ HOXA9 is highly expressed.…”
Section: Discussionmentioning
confidence: 99%
“…MEIS1, a TF belonging to the TALE homeobox family, is essential for cell growth and development (Li et al 2022 ). In several solid tumors, such as breast, colorectal, human esophageal squamous cell, ovarian, and prostate cancers, MEIS1 plays an oncogenic role (Blasi and Bruckmann 2021 ). Moreover, it has been observed that MEIS1 is upregulated in neuroblastoma and glioma cells, supporting cell survival and proliferation (Berdasco et al 2009 ; Zha et al 2014 ; Vastrad et al 2017 ; Girgin et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these biological aspects, an additional review proposes the application of the groundbreaking theory to complement the biophysical model of Hox gene collinearity during development and evolution [ 8 ]. Finally, one review discussed the combinatorial role of HOX and MEIS proteins in leukemia and solid tumors [ 9 ]. Together, these two reviews underline the value of considering HOX proteins and the HOX-MEIS partnerships from a therapeutic perspective in cancer.…”
mentioning
confidence: 99%